Molecular and clinical dissection of CD24 antibody specificity by a comprehensive comparative analysis - Kristiansen, Glen; Machado, Eda; Bretz, Niko; Rupp, Christian; Winzer, Klaus-Jürgen; König, Anne-Kathleen; Moldenhauer, Gerhard; Marmé, Frederik; Costa, Julia; Altevogt, Peter (Laboratory investigation, 2010)
CD24 is a small, highly glycosylated cell surface protein that is linked to the membrane through a glycosyl-phosphatidylinositol anchor. It is overexpressed in many human carcinomas and its expression is linked to bad prognosis. Lately, lack or low expression of CD24 was used to identify tumor stem cells resulting in conflicting data on the usefulness of this marker. In many immunohistochemical studies, the mAb SN3b was used but the epitope and specificity of this antibody have never been thoroughly investigated. In other studies based mainly on cytofluorographic analysis, the mAb ML-5 was applied. In this study, we compared the epitope of mAb SN3b to the CD24 mAbs SWA-11 and ML-5 that both bind to the core protein of CD24. Using tissue microarrays and affinity-purified CD24 glycoforms, we observed only a partial overlap of SN3b and SWA11 reactivity. The mAb SN3b recognizes sialic acid most likely on O-linked glycans that can occur independently of the CD24 protein backbone. The SN3b epitope was not related to common sialylated cancer-associated glycan structures. Both SN3b epitope positive or negative CD24 glycoforms supported the binding of P-selectin and Siglec-5. In breast cancer, the SN3b reactivity was associated with bad prognosis, whereas SWA11 was not. In renal cell cancer, the SN3b epitope was completely absent but SWA11 reactivity was a prognostic factor. Our results shed new light on the tumorbiological role of CD24 and resolve discrepancies in the literature related to the use of different CD24 mAbs.